Memorable tourism experience of non-muslim tourists towards mosque tourism - Abdul Rafar, Mohd Fariz; Md Sawari, Siti Salwa (2019)
Places of worship have been magnets for visitors for hundreds of years. Iconic mosques, churches and cathedrals globally functions as both religious or sacred activities centre as well as being famous attractions. One of the most popular destinations for both Heritage and Islamic tourism are Mosques. Mosque Tourism is a branch of both Religious and Heritage Tourism which has attracted both Muslims and Non-Muslims alike. Although research have been conducted on Muslim visitors’ tourism to Islamic holy sites, previous literature is surprisingly silent on the topic of non-Muslim visitors engaging in tourism at Islamic sites. Thus, this study aims to explore the experiences that interests non-Muslim travelers when engaging with Mosque Visits. A total of 2 respondents that are non- Muslim tourists, aged 18 and above and had previously engage in Mosque Tourism were interviewed using semi-structured interviews. The data is then analyzed thematically according to the seven domains of Memorable Tourism Experience (MTE) namely hedonism, refreshment, local culture, meaningfulness, knowledge, involvement, and novelty. The result shows that the memorable tourism experience of a non-Muslim tourists when visiting mosques are Novelty, Local culture and Knowledge. This study is significant in gathering information on the important considerations that has to be taken into account by destination managers, particularly Mosques in order to accommodate non-Muslim tourists’ needs and meet their expectations in order to improve the overall tourists experience as well as share more about the Islamic religion.